The Necessity of Establishing Business Ethics in International Economics and Trade Major in University - Li, Jiang; Shi, Yanlong (International Journal of Management and Education in Human Development, 2022)
Business Exchange is a series of commodity exchange activities organized and carried out by human individuals to obtain social materials, information and energy. It is realized using benefit exchange. Business activities meet the diverse needs of people in production and life and promote the comprehensive and in-depth development of Chinese society. With the advancement of science and technology, China's economic growth rate and scale continue to expand, especially with the rapid growth of the foreign trade industry. In 2021, the total global trade was 28.5 trillion US dollars, and China's total international trade was 6.06 trillion US dollars, accounting for 21.26 percent of the total global trade. In 2013, President Xi Jinping put forward the "Belt and Road" strategy to coordinate and drive the development of China's neighboring countries. As the "golden signboard" of the Belt and Road, the throughput of China-Europe freight trains has been increasing year by year. In the first quarter of 2022, a total of 1,941 freight trains and 174,000 containers were delivered from China, up 15% and 18% respectively compared with the beginning of the year. In March 2022, the total number of freight trains and cargo transportation of China-Europe freight lines repeatedly hit record highs in the same period. The rapid growth of the foreign trade industry has driven the demand gap for high-quality international trade professionals to increase gradually. Therefore, the basis of teaching students to abide by trade rules and be familiar with foreign trade procedures, it is extremely important to open Business Ethics courses.The innovation of this paper is reflected in the following aspects: first, it creates the precedent of setting up Business Ethics in international economics and trade majors in Chinese universities; Second, it puts forward the similarities and differences between Business Ethics and traditional ideology and morality. Three is by building "in the international economic and trade professional undergraduate teaching Business Ethics construction model and the feasibility of the implementation path" analysis framework, system to study the problem of Business Ethics influence on international trade professionals, compared to the previous research, this article more detailed combing the theory, urgency, necessity and the possibility of internal logic, conducted from the perspective of explanation Innovation.